ULASAN MENGENAI KUAT LEKATAN ANTARA NATURAL FIBER REINFORCED POLYMER (NFRP) DENGAN BETON UNTUK PERKUATAN - Shafira Salsabila; Taufiq Saidi; Muttaqin Hasan (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2022)
Retrofits and reinforcements are needed in structures that have experienced a decline in performance to continue to meet their strength requirements. Reinforcement of reinforced concrete structures can use the method of strengthening with Fiber Reinforced Polymer (FRP) which is made from synthetic fibers. But now there is a new innovation, namely FRP which is made from natural fibers. The use of natural fibers as the basis for composite materials can reduce the negative impact on the environment because the manufacturing process is environmentally friendly and renewable when compared to synthetic-based FRP. Some natural fibers that have been explored and researched consist of bamboo fiber, bagasse, hemp, abaca, and several other fibers that have high tensile strength values. The purpose of this study was to examine the characteristics of natural fibers which include tensile strength and the effect of NFRP material on structural reinforcement by externally bonding methods from various references and also to study the failure modes that occur in the test object. Furthermore, it is presented in a literature regarding the bond strength between NFRP material and concrete. There are several studies on bond strength that have been collected and seen various differences between the studies on the bond strength. Most of the composite process is the attachment of composites to the concrete surface by the hand lay-up method.